Unraveling the Effects of AI Usage on Burnout among Programmers: An Apriori Algorithm Data Mining Approach - Muhammad Fardan; Ana Sulistiana Alwi; Khalil Mubaraq Darwing; Dewi Fatmarani Surianto; Putri Nirmala; Nurrahmah Agusnaya (Information Technology Education Journal, 2025)
Burnout is a growing problem across various industries, particularly among programmers who face high workloads and prolonged stress. In this digital era, the use of technologies such as AI can be a solution to reduce workloads and improve employee well-being. This study aims to identify how the use of AI can reduce burnout levels in programmers. The method used is a cross-sectional research design with data collection through a survey using the Google Form platform, and data analysis using descriptive techniques and the Apriori algorithm to find patterns in the relationship between the duration of AI use, workload, and burnout levels. The results show that the use of AI can help reduce burnout levels by lowering workloads, providing a basis for more effective interventions in the workplace.